Analisis Wacana "Lha...Dalah!" Harian Joglosemar Edisi April dan Mei Tahun 2016 Sebagai Bahan Ajar Teks Anekdot Kelas X Sma - Purwanto, Edy; , Drs. Agus Budi Wahyudi, M.Hum (2016)
This study describes the discourse of "Lha..dalah!" In the daily Joglosemar as teaching materials text anecdotes especially the high school level class X. This study uses qualitative descriptive approach and match with. The purpose of research: (1) mentions discourse "Lha...dalah!" daily Joglosemar that can be used as teaching materials text anecdote in class X SMA, (2) explain the steps discourse "Lha dalah" Daily Joglosemar as teaching materials text anecdote class X High School. The data in the form of discourse "Lha...dalah!" Joglosemar daily as teaching materials text anecdotes. Technique data collecting by documentation, technical see, and technical notes. The data analysis using techniques and match with the basics: sorting technique decisive element (PUP) and methods of unified referential with the basic techniques as a referent power pilah. Triangulation theory used to test the validity of the data. The results in this study as follows (1) Found Full text structure anecdotal and incomplete in discourse "Lha...dalah!" full of anecdotes text structure includes abstract, orientation, crisis, reaction, and a coda that can be used as teaching materials text anecdotes. Of the 35 texts found full of anecdotes text structure amounted to 7 text and text structures totaling 28 anecdotes incomplete text. (2) Found discourse "Lha...dalah!" Through the characteristics of linguistic text anecdote is there are 11 text using a word that shows the story of the past / past, 21 text indicating interjection in the story, and 12 texts that show interjection in the story. The results of this study be used as teaching materials anecdotal text SMA particular class X KD 3. 4. Evaluate text anecdotes based on the principles of both oral and written texts. Keywords: structural anecdotes text, discourse "Lha...dalah!", the text of anecdotes.